Strategi pemasaran digital marketing berperan dalam meningkatkan popularitas media berita online Suaralahat.com di Provinsi Sumatera Selatan - Rahayu, Suharni; Astria, Kenny (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The goal of this study was to figure out and analyse the digital marketing strategy for the online news site Suaralahat.com in South Sumatra Province, which is becoming more and more popular. For this kind of research, the qualitative method is used. The researcher himself is the research tool, and interviews and observations help the researcher get valid data. The population used is the total number of people who read Suaralahat.com over a 10-month period, which was 34,778 people. This study's sample The number of samples in this study, 99.7 people, which were rounded up to 100, was found by using the Slovin formula. SWOT analysis is the method used to look at the data. Based on the results of research that used SWOT analysis on Suaralahat.com, it looks like the company's use of digital marketing strategies is a great way to get more people to notice it. This is because the SWOT analysis diagram shows that the first quadrant, which is a very profitable situation, has the highest total score. Suaralahat.com has opportunities, but it also needs to minimise its weaknesses and deal with a number of threats.